School Culture Management in Addressing Microaggressions: A Case Study from Indonesian Inclusive Education - Ade Putra; Achadi Budi Santosa; Enung Hasanah (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study analyzes school culture management strategies in tackling microaggressions to create a safe and inclusive learning environment. The study used a qualitative approach with a case study design at SD Muhammadiyah Danunegaran, Yogyakarta. Data were obtained through in-depth interviews, observations, and document analysis with informants of the principal, three classroom teachers, and one special assistant teacher. Then, the data were analyzed using thematic analysis techniques assisted by ATLAS.ti software. The results show that the strategies implemented include instilling and habituating values, strengthening school community involvement, strengthening and controlling social norms, providing personal approaches and support, and utilizing visual media. The main obstacles were teachers' limited competence in maintaining consistent role modeling and the negative influence of families that did not support inclusive values. Supporting factors included a strong religious culture and a homogeneous school social environment. Evaluations are conducted regularly and collaboratively to ensure program sustainability. This strategy has fostered empathy, cultivated positive habits, and created an inclusive learning climate. The sustainability of school culture management responsive to diversity requires improving teacher competence and strengthening synergy with families. Theoretically, this research contributes to the literature on school culture management in the context of inclusive education. These findings can be used as a reference for developing teacher competencies and school policies that support a diversity-friendly learning environment.